The Politics of Data Portals in Inter- And Transdisciplinary Research - Vila Seoane, Maximiliano; Hornidge, Anna-Katharina (Journal of Information Systems and Technology Management, 2021)
In this paper, we argue that the ongoing processes of datafication and dataism are constraining initiatives to construct open data portals contributing to inter- and transdisciplinary research. The former overvalues quantitative data, whereas the latter reinforces the belief that ‘raw data’ is neutral and apolitical, ignoring how data is processed. Based on the case study of an open data portal being developed at an inter- and transdisciplinary research institute, we argue that datafication and dataism are highly problematic trends, because they marginalize qualitative data employed in critical, constructivist, and other interpretive methods, thereby limiting the possibility of complementing and extending each other. Nonetheless, we also maintain that these trends are not technologically determined but are modifiable, based on the design of data portals. Accordingly, we conclude by offering suggestions for constructing data portals, such as opening up the design process and democratizing standards.